Electroflotation of ultrafine chalcopyrite particles with sodium oleate collector. (May 2018) - Makuei, Fidele; Tadesse, Bogale; Albijanic, Boris; Browner, Richard
Highlights: Electroflotation of ultrafine chalcopyrite with sodium oleate was investigated. Electrochemical oxidation of chalcopyrite surface plays a key role. Interaction between chalcopyrite and oleate is through chemisorption. Current density, pH and oleate concentration markedly affect chalcopyrite recovery. Abstract: The electroflotation behaviour of ultrafine chalcopyrite particles was investigated using a mechanically agitated cell. The use of sodium oleate as collector proved effective in the flotation of particles of average size of 5 µm. The results showed that chalcopyrite recovery increases with increasing pulp pH, and current density, but decreases with increasing pulp density. The successful flotation of chalcopyrite with oleate might be attributed to its electrochemical surface oxidation, resulting in the formation of cupric and ferric oxide species. Chemisorption of oleate ions onto oxidized chalcopyrite surface is suggested to be the main cause for the increase in chalcopyrite recovery.